2016
DOI: 10.1097/prs.0000000000001866
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Radiation Therapy, Lymph Node Dissection, and Hormonal Therapy on Outcomes of Tissue Expander–Implant Exchange in Prosthetic Breast Reconstruction

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…Impact of several adjuvant approaches on surgical outcomes after second stage in TE/implant reconstruction is the topic of a recent study (6). A large dataset of prospectively collected NSM TE/two-stage cases were analyzed, by means of multivariate analyses adjusting for several parameters, with a 26-month median follow-up after TE exchange for implant.…”
mentioning
confidence: 99%
“…Impact of several adjuvant approaches on surgical outcomes after second stage in TE/implant reconstruction is the topic of a recent study (6). A large dataset of prospectively collected NSM TE/two-stage cases were analyzed, by means of multivariate analyses adjusting for several parameters, with a 26-month median follow-up after TE exchange for implant.…”
mentioning
confidence: 99%
“…Among the studies with indirect data analysis, radiotherapy was the main factor associated with implant loss, which was shown in seven papers [20][21][22][23][24]27,30 . According to a metanalysis published in 2015, the relative risk of reconstructive surgery failure in irradiated patients is 2.58 (95% confidence interval -95%CI 1.86-3.57).…”
Section: Yii and Khoomentioning
confidence: 99%
“…The available options include tamoxifen, aromatase inhibitors, and fulvestrant (11)(12)(13)(14)(15)(16). A prospective randomized trial performed in 1995, comparing modified radical mastectomy to hormone therapy followed by modified radical mastectomy found that there was no significant difference in the risk of complications and that immediate breast reconstruction was not an independent predictor of complications (17).…”
Section: Hormonal Therapymentioning
confidence: 99%
“…The optimal timing of radiotherapy and breast reconstruction is still a subject of debate (11). Patients receiving the alloplastic prosthesis, form a distinct group than those treated with autologous tissue reconstruction.…”
Section: Radiation Therapymentioning
confidence: 99%